Development and Performance Evaluation of Enhanced Piezo-Electric Sensor Cum Energy Harvester Based on Flexural Strain Amplification in Real-Life Field Conditions - Sreenitya Singamsetty; Naveet Kaur; Suresh Bhalla (Sensors)
Driven by technological advancements and accelerated infrastructure development, an increase in the need to monitor the performance of prominent structures such as bridges, metro-corridors, and sea-link bridges is being advocated by experts to predict and minimize any hazards resulting from the degradation of the structures over time. However, accessing and replacing the batteries becomes problematic and expensive when the sensors are instrumented in remote areas of the bridge structures, especially when the sensors are embedded. For these reasons, a strong case can be made for harvesting and storing ambient energy from the surroundings to drive the sensors for structural health monitoring (SHM). This study aims to introduce a new trapezoidal strain-amplifying sensor/energy harvester (TSAH) for civil engineering structures that uses flexural strain amplification to enhance energy harvesting from structural vibrations. TSAH also serves as a sensor for integrated energy harvesting and SHM. This article examines the influence of the geometric properties of TSAH on strain amplification via numerical investigations under a specific set of external loads. Based on numerical studies, the sensors are bonded to the trapezoidal strain-amplifying plate to develop and assess the TSAH. Experimental investigations were carried out first in the laboratory to evaluate the effectiveness of the TSAH over the directly bonded (DB) sensors with two different types of piezo-transducers for energy harvesting. The host structure was exposed to impact and shaker vibrations for the laboratory research. For the various scenarios taken into consideration in the study, the typical amplification factor for peak voltage is determined to be between 1.45 and 3.75, while for the power, it is between 1.09 and 6.08. Further, for field verification, the TSAH configuration was evaluated on a real-life bridge structure, viz the Chipiyana rail over-bridge (ROB), Asia’s heaviest steel ROB located on the Delhi–Meerut expressway. The field experiments also establish the superior performance of TSAH, with an amplification factor ranging from 1.75 to 3.75 for peak voltage and 3.75 to 5.53 for peak power. As compared to the previously proposed curved configuration in the literature, the TSAH configuration is suitable for brittle sensors as well. Its ability to be permanently bonded by epoxy/welding, or temporarily using magnets, bolts, or clamps, offers it versatility over other surface bonded/embedded configurations. As a result of this, it imparts reusability in case of any damage, which promotes the goal of sustainability.